Inter-rater reliability of modified hand mobility in scleroderma test - Tore, Nurten Gizem; Sari, Fulden; Sarac, Devrim Can; Yentur, Songul Baglan; Satis, Hasan; Guler, Aslihan Avanoglu; Oskay, Deran (Wiley, 2020)
Aim Systemic sclerosis (SSc) is a chronic autoimmune disease of unknown etiology characterized by excessive collagen production, endothelial cell injury, microvascular obliteration, cutaneous fibrosis and progressive visceral disease. The hands are frequently involved during the progression of the disease, with symmetrical skin thickening as a prominent feature. Modified hand mobility in scleroderma (mHAMIS) test is a measurement method to assess hand mobility in patients with SSc. Knowing the inter-rater reliability of the instrument is important in order for the results from different examiners to be accurately interpreted. The aim of this study was to test inter-rater reliability of the mHAMIS test. Method Hand mobility for both hands was assessed in 25 female patients with SSc by 2 physiotherapists who have different years of experience. Patients who had flexion contracture in at least 1 finger and undergone hand surgery in the last year due to any injuries, were excluded from the study since hand mobility was prevented. Inter-rater reliability was determined using intra-class correlation coefficients (ICCs). Result The ICCs were excellent between raters for dominant and non-dominant hands. The values were 0.92 and 0.93, respectively. Conclusion The inter-rater reliability of the mHAMIS was found to be excellent. This research contributes to the literature by proving that the test can be used without causing bias in clinical trials.
Keywords: hand mobility; inter-rater; mHAMIS; reliability; systemic sclerosis